2014
DOI: 10.4254/wjh.v6.i8.613
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs in patients with non-alcoholic fatty liver disease

Abstract: AIM:To identify novel non-invasive biomarkers for non-alcoholic fatty liver disease (NAFLD). METHODS:Twenty patients with histologically proven NAFLD and 20 controls were included. All NAFLD cases were scored using the NAFLD activity score. The relative expressions of miR-197, miR-146b, miR-10b, miR181d, miR-34a, miR-122, miR-99a and miR-29a were analyzed using real-time polymerase chain reaction. RESULTS:Serum levels of miR-181d, miR-99a, miR-197 and miR-146b were significantly lower in biopsy-proven NAFLD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 22 publications
1
65
0
1
Order By: Relevance
“…miR-197 was also lower in biopsy-proven nonalcoholic fatty liver (Celikbilek et al, 2014), primary biliary cirrhosis (Ninomiya et al, 2013), multiple sclerosis1 (Margareta Jernås et al, 2013), uterine leiomyoma (Ling et al, 2015a), type 2 diabetes (Zampetaki et al, 2010) and increased in placentas of preeclampsia (Choi et al, 2013), Graves' disease (Qin et al, 2015). Furthermore, miR-197, in hepatitis B virus infected patients, gradually decreased along with the severity of liver disease symptoms.…”
Section: Mir-197 In Othersmentioning
confidence: 88%
See 1 more Smart Citation
“…miR-197 was also lower in biopsy-proven nonalcoholic fatty liver (Celikbilek et al, 2014), primary biliary cirrhosis (Ninomiya et al, 2013), multiple sclerosis1 (Margareta Jernås et al, 2013), uterine leiomyoma (Ling et al, 2015a), type 2 diabetes (Zampetaki et al, 2010) and increased in placentas of preeclampsia (Choi et al, 2013), Graves' disease (Qin et al, 2015). Furthermore, miR-197, in hepatitis B virus infected patients, gradually decreased along with the severity of liver disease symptoms.…”
Section: Mir-197 In Othersmentioning
confidence: 88%
“…Thus, it was of great concern to investigate the roles and potential mechanisms of key miRNAs in tumorigenic driver pathways. Among them, miR-197, transcribed from the genomic region of chromosome 1p13.3, was found to be significantly dysregulated in a wide range of diseases, such as lung cancer (Remon et al, 2015), breast cancer (Shaker et al, 2015), ovarian cancer (Zou et al, 2015), hepatocellular carcinoma (HCC) , colorectal cancer , thyroid cancer (Weber et al, 2006), head and neck carcinoma (Dai et al, 2011), prostate cancer , follicular thyroid carcinoma (FTC) (Weber et al, 2006), non-alcoholic fatty liver disease (Celikbilek et al, 2014), primary biliary cirrhosis (Ninomiya et al, 2013). Furthermore, increasing evidences had confirmed that miR-197 played a vital role in cell proliferation, apoptosis, differentiation, metastasis and drug resistance, as well as other cellular processes through interacting with particular RNA species (Huang et al, 2014) (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, miR-197 has been shown to promote pulmonary metastasis for non-small cell lung cancer [37,46]. miR-197 also participates in the development of a number of types of cancer [26][27][28][29][30][31][32][33][34], including HCC [29,30], indicating the role of miR-197 in cancer.miR-197 also participates in liver fibrosis [35,36], in which Wnt/β-catenin signaling also plays a central role [47].…”
Section: Discussionmentioning
confidence: 84%
“…Dysregulation of miRNA secretion is associated with diverse pathological conditions, including diabetes [25] , liver disease [73] , tissue injury [74] , and cancer [11] . Accordingly, changes in extracellular miRNA profiles may reflect molecular alterations in the cells from which they are derived, and therefore provide unique pathological signatures that aid in disease diagnosis and inform therapeutic strategy.…”
Section: Mirnas As Biomarkers For Cancermentioning
confidence: 99%